Weight Cycling and Dieting Behavior in Fitness Club Members - Haakstad, Lene A. H.; Stensrud, Trine; Rugseth, Gro; Gjestvang, Christina (Frontiers in Endocrinology, 2022)
Background: Along with the rising prevalence of high body-mass index (BMI), there is also increased emphasis on leanness and fitness. Both these trends suggest that many individuals are concerned about weight management and may try to lose weight. Yet, no research has been carried out in the social context of a fitness club. Using data from the research project “Fitness clubs - a venue for public health?”, we aimed to describe weight cycling and energy-restricted dieting in men and women at start-up of fitness club membership, and to investigate influencing factors (age, BMI, educational level, self-classified overweight/obesity, compliance with nutritional guidelines, unhealthy weight control strategies and self-perceived health (SPH)). Methods: In a cross-sectional online survey, 250 men and women from 25 fitness clubs in Oslo, reported anthropometrics, self-classified weight group, weight cycling, weight loss/gain, eating habits/dieting, and background/health information. Enrollment was limited to adult (≥18 years) novice exercisers (exercising <60 min/week at a moderate or vigorous intensity or brisk walking <150 min/week, the past six months) with less than four weeks of membership. Factors associated with weight cycling were examined using simple and multiple logistic regression, separated for men and women. Results: In both sexes (mean age: 36.4 ±11.3 years), a high number reported substantial weight fluctuation (+/-5 kg) the past 12 months (men: 50% and women: 62%, p=0.056) and unhealthy weight control strategies (men: 24.8% and women: 47.2%, p<0.001). Weight cyclers had a higher mean BMI compared with non-cyclers (27.0 ± 4.9 versus 25.4 ± 3.6, p= 0.003). Further, the difference in body weight was 6.7 kg (CI 2.2 to 10.8, p=0.004) and 10.8 kg (CI 5.8 to 15.8, <0.001) in men and women, respectively. Besides BMI status, self-classified overweight/obesity was the strongest predictor of reporting weight cycling (men: OR 5.54, 95% CI 2.03 to 15.12, p<0.01 and women: OR 7.17, 95% CI 2.48 to 20.68, p<0.001). Conclusion: In novice exercisers, a large proportion reported weight cycling and unhealthy weight control strategies, and both were more prevalent in women than in men. Self-classified overweight was found to be the most important factor influencing weight cycling.